Comparative evaluation of effectiveness of three desensitizing tooth pastes for relief in the dentinal hypersensitivity - Disha Bansal; Mrinalini Mahajan (Wolters Kluwer Medknow Publications, 2017)
Context: Dentinal hypersensitivity is a sharp pain occurring on exposure of the exposed dentin to various stimuli such as hot, cold, air, tactile, and chemical. Aim: This study aimed to compare the effectiveness of three desensitizing pastes in the treatment of dentinal hypersensitivity. Materials and Methods: A total of 45 individuals (with two teeth per patient) were considered for this study and randomly divided into three groups, Group 1: treated with 5% NovaMin-containing toothpaste, Group 2: treated with 8% arginine-containing toothpaste, and Group 3: herbal desensitizing toothpaste. Using tactile stimulus and air stimulus, the sensitivity scores were recorded on visual analog scale (VAS), immediately after paste application, then at 2 weeks, and then at the end of 4 weeks and compared. Results: There was a significant change in the VAS scores in Group 1 when compared to Group 2 and Group 3. Group 1 showed better reduction in the hypersensitivity in long term. Statistical Analysis: One-way ANOVA test, post hoc Tukey test, and post hoc Bonferroni test were used for statistical analysis. Conclusion: Desensitizing pastes can be an effective and economical option in the treatment of the dentinal hypersensitivity.